The Importance of an In-depth Study of Immunoglobulin Gene Rearrangements When Ascertaining the Clonal Relationship between Concomitant Chronic Lymphocytic Leukemia and Multiple Myeloma - Trudel, Stéphanie; Ghamlouch, Hussein; Dremaux, Julie; Delette, Caroline; Harrivel, Véronique; Marolleau, Jean-Pierre; Gubler, Brigitte (Frontiers in Immunology, 2016)
Chronic lymphocytic leukemia (CLL) and multiple myeloma (MM) are hematological disorders that occur at different stages of B-cell development. It has been shown that CLL B-cells can differentiate into plasma cells in vitro and in vivo. CLL is the most frequent adult leukemia in the western world. It is a heterogeneous disease, characterized by clonal proliferation and the accumulation of mature CD5+ B lymphocytes (Zenz et al.). MM is a clonal plasma cell malignancy that accounts for more than 10% of all hematologic cancers (Kyle and Rajkumar, 2008). Although secondary cancers (particularly solid tumors (Hasskarl et al.;Morton et al.;Schollkopf et al., 2007)) can occur with CLL and MM, the concomitant occurrence of these two disorders in the same patient is rare (for a review of the few reported cases, see (Alley et al.)). The clonal relationship between these diseases has not always been clarified but is important in terms of understanding the pathogenesis and optimizing treatment. The clonal relationship between CLL and MM can be evaluated by (i) analyzing immunoglobulin heavy chain (IGH) and light chain (IGK, IGL) gene rearrangement, (ii) identifying and comparing somatic mutations, (iii) studying chromosomic aberrations. Nevertheless, immunoglobulin rearrangements must always be interpreted in the light of specific phenomena such as allelic exclusion, B-cell receptor (BCR) revision (VH and DH gene replacement), BCR editing and somatic hypermutations - events that were not considered in previous studies. These issues can be addressed by sequencing the rearranged immunoglobulin genes from sorted populations and interpreting the generated data. In the present study, we evaluated the putative clonal relationship between the two diseases by combining DNA copy number analysis with an assessment of Ig gene rearrangements (clonality assessment, V(D)J sequencing and somatic hypermutation analysis) in highly enriched CD19+ CD5+ (CLL) and CD38+ CD138+ (MM) cell populations. Array comparative genomic hybridization data suggested a possible phylogenic progression from CLL to MM. Moreover, V(D)J sequencing indicated that both CLL and MM cells used the same VH and JH genes but different DH genes. However, in-depth analysis and interpretation of Ig gene rearrangements ultimately suggested that the two diseases had distinct clonal origins.